มุสลิมบางกอกน้อย: พัฒนาการทางประวัติศาสตร์ อัตลักษณ์ ภูมิปัญญา และวิถีวัฒนธรรมอิสลามในเมืองหลวง - ผลดี ผู้ช่วยศาสตราจารย์ ดร.สำราญ (Journal of Humanities and Social Sciences Thonburi University, 2018)
บทคัดย่อ การวิจัยครั้งนี้ มีวัตถุประสงค์สำคัญ 2 ประการคือ 1) ศึกษาภูมิหลัง พัฒนาการทางประวัติศาสตร์ อัตลักษณ์ ภูมิปัญญา และวิถีวัฒนธรรมของชุมชนมุสลิมในพื้นที่ริมคลองบางกอกน้อย 2) วิเคราะห์กระบวนทัศน์การปรับตัว การธำรงอัตลักษณ์ การอนุรักษ์มรดกภูมิปัญญา และวิถีวัฒนธรรมความเป็นชุมชนมุสลิมริมฝั่งคลองบางกอกน้อยภายใต้เงื่อนไขและบริบททางประวัติศาสตร์ เป็นการวิจัยเชิงคุณภาพ โดยศึกษาข้อมูลจากเอกสาร และการศึกษาภาคสนาม และนำเสนอผลการวิจัยแบบพรรณนาวิเคราะห์ ผลการวิจัยพบว่า บรรพบุรุษของชุมชนมุสลิมบางกอกน้อยคือกลุ่มคนที่อพยพมาจากกรุงศรีอยุธยาเมื่อ พ.ศ.2310 เป็นชุมชนที่เคร่งครัดในศาสนาอิสลาม นิกายซุนนีห์ มีมัสยิดหลวงอันซอริซซุนนะห์เป็นศูนย์กลางของชุมชน โดยธำรงอัตลักษณ์ที่สะท้อนผ่านการแต่งกายและการปฏิบัติศาสนกิจ มรดกภูมิปัญญาที่สำคัญคือ อาหารมุสลิมและการทำที่นอนยัดนุ่น มีวิถีวัฒนธรรมที่ยึดมั่นตามคำสอนของศาสนาอิสลามอย่างเคร่งครัด และกระบวนทัศน์การปรับตัวที่สำคัญคือการปลูกฝังแนวคิดและวิถีการดำรงตนตามแนวทางของศาสนาอิสลามไว้ในระบบการศึกษา ส่งผลให้เป็นกลุ่มชาติพันธุ์ที่เข้มแข็งสามารถดำรงตนและพื้นที่ทางสังคมได้อย่างภาคภูมิ คําสําคัญ: มุสลิมบางกอกน้อย, พัฒนาการทางประวัติศาสตร์, กระบวนทัศน์การปรับตัว Abstract This research had two main objectives including 1) to study the background, historical development, identity, local wisdom and local culture of Muslim community in Bangkok Noi Canalside, and 2) to analyze the paradigm in adaptation, the remaining of identity, conservation of local wisdom and ways of local culture of the Muslim community in Bangkok Noi Canalside in accordance with historical contexts. This research employed qualitative methods including reviewing and collecting related documents and fieldwork study. The data was then analyzed, synthesized and presented in descriptive research analysis. The results showed that ancestors of the Muslim community in Bangkok Noi migrated from Ayutthaya since the period of the second loss of the Ayutthaya City. This Muslim community has strongly adhered to the Islam Sunni. Additionally, the establishment of Ansorissunnah Royal Mosque has been the center of the community. Remarkably, the community has remained their identity through the way of dressing and performing strictly in accordance with the Islam religion. Significant local wisdom of the community is Muslim food and making white silk cotton mattress. For the ways of culture, it has been strictly followed the principle of Islam. Nevertheless, the significance of paradigm in adaptation is to build awareness and ways of living following the Islam, which have been embedded in the educational system. As a consequence, these practices have constructed the strength of the ethnic group and have effectively supported the existence and maintained their social zone. Key words: Muslim Bangkok Noi, historical development, paradigm in adaptation